2023
DOI: 10.3390/ijms24044113
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Primary Human Bronchial Epithelial 3D Cell Culture with Donor-Matched Fibroblasts and Comparison of Two Different Culture Media

Abstract: In vitro airway models are increasingly important for pathomechanistic analyses of respiratory diseases. Existing models are limited in their validity by their incomplete cellular complexity. We therefore aimed to generate a more complex and meaningful three-dimensional (3D) airway model. Primary human bronchial epithelial cells (hbEC) were propagated in airway epithelial cell growth (AECG) or PneumaCult ExPlus medium. Generating 3D models, hbEC were airlifted and cultured on a collagen matrix with donor-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…This is important for electrophysiological studies that rely on the integrity of the epithelial barrier. Interestingly, we observed that PN-ALI differentiated epithelia had a lower TEER compared to AB-ALI differentiated epithelia, consistent with previously published studies and likely attributable to a combination of reduced expression of sealing claudins and increased electrogenic ion transport 12 , 13 , 22 , 23 . Conversely, the higher TEER in AB-ALI differentiated cultures could be due to a squamous epithelium phenotype, which has been shown to confer higher TEER values 12 , 24 .…”
Section: Discussionsupporting
confidence: 91%
“…This is important for electrophysiological studies that rely on the integrity of the epithelial barrier. Interestingly, we observed that PN-ALI differentiated epithelia had a lower TEER compared to AB-ALI differentiated epithelia, consistent with previously published studies and likely attributable to a combination of reduced expression of sealing claudins and increased electrogenic ion transport 12 , 13 , 22 , 23 . Conversely, the higher TEER in AB-ALI differentiated cultures could be due to a squamous epithelium phenotype, which has been shown to confer higher TEER values 12 , 24 .…”
Section: Discussionsupporting
confidence: 91%
“…One of the most challenging organs to mimic is the lung [18,19]. Maurer J. et al [20] proposed a novel complex 3D airway model for the study of respiratory diseases. Primary human bronchial epithelial cells were cultured on a collagen matrix with donor-matched bronchial fibroblasts, and characterized for properties and functions of epithelial barrier and ciliated epithelium.…”
mentioning
confidence: 99%